Tailored breast imaging during the first wave and preparedness for the second wave of COVID-19 pandemic (2020)
The pandemic caused by the new Coronavirus has changed the way patient care is provided worldwide. This review focuses on the description of the operational measures implemented in a breast imaging department in accordance with existing recommendations for the treatment of breast cancer during the COVID-19 pandemic to make optimal use of finite resources without interruption of essential imaging services for breast cancer patients. It will also apply during a second-wave of the pandemic, which, according to experts, is inevitable and requires us to be better prepared.